2005
DOI: 10.1007/s11010-005-5778-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of isoniazid on hippocampal NMDA receptors: Protective role of Erdosteine

Abstract: Isoniazid (INH) has neurotoxic effects such as seizure, poor concentration, subtle reduction in memory, anxiety, depression and psychosis. INH-induced toxic effects are thought to be through increased oxidative stress, and these effects have been shown to be prevented by antioxidant therapies in various organs. Increased oxidative stress may be playing a role in these neurotoxic effects. N-methyl D-aspartat receptors (NMDA) are a member of the ionotropic group of glutamate receptors. These receptors are involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Similar to cases and review in the literature, paranoid delusions were determined prominently in our case. It was determined that INH decreased number of N-methyl-D-aspartate (NMDA) receptors in the hippocampus, and this effect was abolished by addition of erdostein which was an antioxidant molecule in a study performed to enlighten the relationship INH and psychiatric disorders, and with the hypothesis of INH might have toxic effects on oxidative stress (9).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to cases and review in the literature, paranoid delusions were determined prominently in our case. It was determined that INH decreased number of N-methyl-D-aspartate (NMDA) receptors in the hippocampus, and this effect was abolished by addition of erdostein which was an antioxidant molecule in a study performed to enlighten the relationship INH and psychiatric disorders, and with the hypothesis of INH might have toxic effects on oxidative stress (9).…”
Section: Discussionmentioning
confidence: 99%
“…Cicek et al [10] demonstrated that isoniazid, which is known to be neurotoxic, induced a decrease in NR2A levels in the hippocampus that was correlated to an increase in lipid peroxidation, and that endosteine, which is an antioxidant, was able to reverse these effects. In addition, mice carrying a mutation at the Tyr 1325 phosphorylation site, which is largely found in NR2A, showed reduced depression-related behavior [62], suggesting that NR2A may be an important target in studying the pathogenesis of mood disorders and in developing therapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…It is a potent antioxidant and mucolytic pharmacological agent (24,25). Erdosteine inhibits lipid peroxidation (25).…”
Section: Discussionmentioning
confidence: 99%
“…Erdosteine inhibits lipid peroxidation (25). The pharmacological agent, therefore, decreases malondialdehyde (MDA), which is the end product of lipid peroxidation (24). Furthermore, erdosteine maintains free radical scavenging properties (25).…”
Section: Discussionmentioning
confidence: 99%